Application Analysis of Reinforced Soil Technology in Highway Subgrade Engineering - Zhou, Yongzheng (Journal of Theory and Practice of Engineering Science, 2023)
In recent years, the construction scale of highway engineering in China has been continuously expanding, and there are many types of technologies applied in the construction of highway subgrade engineering. Construction units need to use professional technical methods to meet the relevant construction requirements. Reinforced soil technology, as a common technical method in highway subgrade construction, can effectively improve the quality of road structures, maintain significant stability, and meet the basic needs of traffic operation. The article mainly analyzes the application significance of reinforced soil technology and the preparatory work that needs to be done in the early stage, briefly discusses the practical application forms of the technology, and is committed to optimizing the comprehensive construction effectiveness of engineering, laying a good foundation for the development of the transportation field.